Rowing shell drag comparisons - Lazauskas, L. (1997)
We compare the steady, calm-water, total (viscous plus wave) resistance of a variety of popular rowing shells. To estimate the total resistance we use Michell's integral for the wave resistance, the 1957 ITTC line for the skin friction, and a simple empirical formula for the form drag. The hulls examined in the present study are summarised in the following table. In this table, D is the displacement volume, L is the length on the waterline, B is the beam on the waterline, and T is the maximum draft. More hulls will be added when time permits.